Analysis of selected reservoirs functioning in the Wielkopolska region - Mariusz Sojka; Joanna Jaskuła; Joanna Wicher-Dysarz; Tomasz Dysarz (Acta Scientiarum Polonorum. Formatio Circumiectus)
The paper presents the problems related to the functioning of reservoirs in the Wielkopolska province and suggests their possible solutions. The reservoirs chosen as examples include typical dam constructions with a single water body (Jeziorsko, Rydzyna), two water body objects with separated preliminary part (Stare Miasto, Kowalskie, Radzyny) and lateral constructions (Pakosław, Jutrosin). The reservoirs were built in period from 1970 to 2014. They differ in construction, functions and water management rules. Analysis of the main problems related to the reservoir functioning is aimed at finding ways of improving the construction of new reservoirs that would satisfy increasingly stringent environmental and legal restrictions and the methods of water management in the reservoirs. On the basis of a questionnaire filled in by the reservoir operators, the main problem is water quality. Especially the huge inflow of biogenic compounds causes blooms of algae and overgrowth with riparian vegetation. Some difficulties are also related to management of the reservoirs of multi-purpose operation. It is difficult to take into account the requirements of environmental flow maintenance, flood protection, water supply for agriculture and water use for tourism and recreation and hydropower generation, etc.